The violation of women's language features used by bubblee in Nadiya Hussain's the secret lives of the Amir sisters - Nuly Ariane (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/yna, c.1